Differential Game and Simulation Study on Management Synergy of Regional Coal Mine Emergencies in China. (30th November 2021) - Hao, Yu; Sun, Chaolun; Wei, Jianping; Gu, Sasa; Zhang, Fan
Abstract : Emergency management of coal mines requires enhanced synergy among departments, institutions, and enterprises, which means overall efficiency in management. Their synergy can effectively lower the cost of emergency management, improve the effectiveness of it, and build a strong joint force for the prevention and control of emergencies. Accordingly, this study established a synergy system for regional coal mine emergency management and analyzed the interest relationship among key stakeholders in the system. Then, it established differential game models of the management synergy, explored the selection process of the behavior strategy of each stakeholder under different situations, and provided important tools for quantitative analysis on emergency management synergy practice. Furthermore, numerical simulation was carried out to analyze the influencing factors of their decision behaviors. The research results are of great significance for the comprehension of the evolution mechanism for the emergency management synergy of coal mines, the assistance for the government in determining the optimal method in emergency management synergy, the mobilization of the stakeholders, and the improvement of the current situation of emergency management synergy of coal mines in China.